2023
DOI: 10.1111/1541-4337.13158
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of lipid oxidation in water‐in‐oil emulsions and oxidomics‐guided discovery of targeted protective approaches

Abstract: Lipid oxidation is an inevitable event during the processing, storage, and even consumption of lipid-containing food, which may cause adverse effects on both food quality and human health. Water-in-oil (W/O) food emulsions contain a high content of lipids and small water droplets, which renders them vulnerable to lipid oxidation. The present review provides comprehensive insights into the lipid oxidation of W/O food emulsions. The key influential factors of lipid oxidation in W/O food emulsions are presented s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2025
2025

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(1 citation statement)
references
References 207 publications
0
1
0
Order By: Relevance
“…This indicates the ability of the emulsifier to retain moisture within the cookie samples and, hence, to impart softness to the products. Further, a recent article reported that emulsifiers could substantially control lipid oxidation by regulating the interfacial behavior between oil and aqueous phases . Therefore, the presence of emulsifiers along with oleogel can also contribute to the improved texture and longer shelf life of the cookies.…”
Section: Resultsmentioning
confidence: 99%
“…This indicates the ability of the emulsifier to retain moisture within the cookie samples and, hence, to impart softness to the products. Further, a recent article reported that emulsifiers could substantially control lipid oxidation by regulating the interfacial behavior between oil and aqueous phases . Therefore, the presence of emulsifiers along with oleogel can also contribute to the improved texture and longer shelf life of the cookies.…”
Section: Resultsmentioning
confidence: 99%